Knowledge, Attitude and Practices Towards Exclusive Breastfeeding Among Nursing Mothers in Rural Areas of Akwa Ibom State: A Cross-Sectional Study - U. A. Asa (JOURNAL OF HUMANITIES AND SOCIAL POLICY, 2026)
Objective: The study assessed knowledge, attitude and practices towards exclusive breastfeeding among nursing mothers in rural areas of Akwa Ibom State. Research Design: Descriptive cross-sectional study design. Sample and Method: A researcher-developed questionnaire, with items covering the specific objectives of the study, was administered to 240 nursing mothers using a two-stage sampling procedure provided the quantitative data for the study. Results: Results of data, analyzed using descriptive statistics, indicated that 59.6% of the nursing mothers had poor knowledge about exclusive breastfeeding; 82.5% had a positive attitude towards exclusive breastfeeding; 83.3% did not take advice from health personnel before breastfeeding; 89.2% gave pre-lacteal feeds to their last children and 52.17% breastfed their children on demand. Recommendation: It is recommended that both Governmental and Non-Governmental agencies in the State embark on targeted community-based enlightenment programmes targeted at nursing mothers in the rural areas of Akwa Ibom State.